Odpowiedź:
a)
-3 2/3 + (-2 1/4) = -3 8/12 - 2 3/12 = -5 11/12
b)
3 1/4 - (-4,5) = 3,25 + 4,5 = 7,75
c)
-7 1/5 + 2 1/2 = -7,2 + 2,5 = -4,7
d)
3 1/7 - 5 1/2 = 3 2/14 - 5 7/14 = -2 5/14
e)
-2 1/3 - 2 1/2 = -2 2/6 - 2 3/6 = -4 5/6
f)
-6,5 - (-8 3/4) = -6,5 + 8,75 = 2,25
g)
5,2 - 8 3/5 = 5,2 - 8,6 = -3,4
h)
-2 7/9 + (-8 5/9) = -2 7/9 - 8 5/9 = -10 12/9 = -11 3/9 = -11 1/3
i)
-9,5 + (-2 1/2) = -9,5 - 2,5 = -12
j)
4 2/3 - (-3 5/6) = 4 4/6 + 3 5/6 = 7 9/6 = 8 3/6 = 8 1/2
k)
6 1/3 - 9,5 = 6 1/3 - 9 1/2 = 6 2/6 - 9 3/6 = -3 1/6
l)
-2 3/4 + 7 1/4 = -2 3/4 + 6 5/4 = 4 2/4 = 4 1/2
Szczegółowe wyjaśnienie: